Macroscopic assembled graphene nanofilms based room temperature ultrafast mid-infrared photodetectors - Peng, Li (2023)
Graphene with linear energy dispersion and weak electron–phonon interaction is highly anticipated to harvest hot electrons in a broad wavelength range. However, the limited absorption and serious backscattering of hot-electrons result in inadequate quantum yields, especially in the mid-infrared range. Here, we report a macroscopic assembled graphene (nMAG) nanofilm/silicon heterojunction for ultrafast mid-infrared photodetection. The assembled Schottky diode works in 1.5–4.0 μm at room temperature with fast response (20–30 ns, rising time, 4 mm2 window) and high detectivity (1.6 × 1011 to 1.9 × 109 Jones from 1.5 to 4.0 μm) under the pulsed laser, outperforming single-layer-graphene/silicon photodetectors by 2–8 orders. These performances are attributed to the greatly enhanced photo-thermionic effect of electrons in nMAG due to its high light absorption (~40%), long carrier relaxation time (~20 ps), low work function (4.52 eV), and suppressed carrier number fluctuation. The nMAG provides a long-range platform to understand the hot-carrier dynamics in bulk 2D materials, leading to broadband and ultrafast MIR active imaging devices at room temperature. (Figure presented.).